Slurry material for inhibiting spontaneous combustion of coal as well as preparation method and application of slurry material
By using calcium oxide-containing slurry materials prepared by fly ash, carbon dioxide and water, the existing slurry materials have been solved, and the efficient and environmentally friendly coal spontaneous combustion inhibition effect is achieved.
Patent Information
- Application Number
- CN202411517649.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-02-14
AI Technical Summary
The existing slurry materials that inhibit coal spontaneous combustion are costly, have poor fire prevention and fire extinguishing effects, and have problems with environmental pollution.
Fly ash, carbon dioxide and water are used as raw materials to prepare a slurry material containing calcium oxide, which is prepared by stirring and mixing and carbon dioxide introduction to ensure that the pH value of the material is between 7-7.5.
This slurry material can effectively increase the temperature of the spontaneous ignition point of the coal, maintain high integrity and not easily dry and cracked, have good sealing and fire-proof and fire-extinguishing effects, and is environmentally friendly and low-cost.
Smart Images

Figure CN119432402A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of underground fire prevention and extinguishing in coal mines, and in particular relates to a slurry material for inhibiting spontaneous combustion of coal, and a preparation method and application thereof. Background Art
[0002] Coal is the main energy source supporting my country's development, but coal mining faces a serious threat of spontaneous combustion. At present, the fire extinguishing materials for suppressing spontaneous combustion of coal are mainly yellow mud slurry, inhibitor colloid, inert gas and three-phase foam. Yellow mud slurry is easy to make as a fire extinguishing material, but it needs to strip the surface soil, causing serious damage to the ecological environment. In addition, after the water evaporates, the slurry material will dry and crack, and new air leakage channels will be formed at the cracks on the surface of the coal body, resulting in reduced fire prevention and fire extinguishing effect; although the inhibitor colloid has a good fire prevention and fire extinguishing effect, it is expensive and has poor stability, and will cause environmental pollution during use; the fire extinguishing cycle of inert gas is relatively long, and the requirements for on-site airtightness are relatively high, and the place of use is limited; and the scope of use of three-phase foam itself is limited, and the environmental protection and cost-effectiveness of the foaming agent and foam stabilizer must be considered, so it is difficult to promote its use. Summary of the invention
[0003] The present application provides a slurry material for inhibiting spontaneous combustion of coal, and a preparation method and application thereof, aiming to solve the problems of high cost, poor fire prevention and extinguishing effect, and environmental pollution of existing slurry materials.
[0004] In a first aspect of the present application, a slurry material for inhibiting spontaneous combustion of coal is provided, comprising the following preparation raw materials, fly ash, carbon dioxide and water; the mass content of calcium oxide in the fly ash is ≥17%.
[0005] The slurry material described in the present application has good wrapping properties for the coal waste, can increase the temperature of characteristic combustion gases such as CO and C2H4, and increase the spontaneous combustion ignition temperature of the coal waste. In addition, the slurry material described in the present application can maintain a high degree of integrity even after losing water, without cracks, and has good sealing properties.
[0006] In addition, the slurry material described in this application uses fly ash, a solid waste discharged by coal-fired power companies, carbon dioxide in waste flue gas, and underground coal mine wastewater as raw materials, which improves the solid waste utilization rate of fly ash, reduces carbon dioxide emissions, and is beneficial to the improvement and maintenance of the ecological environment quality of the mining area.
[0007] According to some embodiments of the slurry material for inhibiting spontaneous combustion of coal described in the present application, the weight ratio of the fly ash to the water is: (30-40): (70-80).
[0008] According to some embodiments of the slurry material for inhibiting spontaneous combustion of coal described in the present application, the amount of carbon dioxide added is sufficient to make the pH of the slurry material be 7-7.5.
[0009] According to some embodiments of the slurry material for inhibiting coal spontaneous combustion described in the present application, the mass content of calcium oxide in the fly ash is 17%-20%, the mass content of silicon dioxide is 40%-50%, and the mass content of aluminum oxide is 19%-25%.
[0010] The second aspect of the present application provides a method for preparing the slurry material for inhibiting spontaneous combustion of coal according to the first aspect of the present application, comprising the following steps:
[0011] (1) mixing fly ash and water to obtain a suspension;
[0012] (2) Under stirring conditions, carbon dioxide is introduced into the suspension to obtain the slurry material.
[0013] The preparation process of the slurry material for inhibiting coal spontaneous combustion described in the present application is simple and suitable for industrial production.
[0014] According to some embodiments of the preparation method described in the present application, in step (1), the mixing temperature is 20-30° C., and the mixing stirring speed is 1400-1500 r / min.
[0015] According to some embodiments of the preparation method described in the present application, in step (2), the stirring speed is 1400-1500 r / min, and the stirring temperature is 20-30°C.
[0016] According to some embodiments of the preparation method described in the present application, in step (2), the introduction rate of the carbon dioxide is 1-2 L / min.
[0017] The third aspect of the present application provides an application of the slurry material for inhibiting coal spontaneous combustion described in the first aspect of the present application or the slurry material for inhibiting coal spontaneous combustion obtained by the preparation method described in the second aspect of the present application in preventing coal spontaneous combustion in mines.
[0018] The slurry material for inhibiting spontaneous combustion of coal described in the present application has a good fire prevention and fire extinguishing effect, can effectively prevent the spontaneous combustion of coal in mines, is easy to use, and has a long-lasting effect.
[0019] According to some embodiments of the application described in the present application, the application is spraying the slurry material onto the surface of coal to prevent the coal from spontaneous combustion.
[0020] According to some embodiments of the application described in the present application, the weight ratio of the slurry material to the coal is (2-4):10. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 To analyze the concentration of C2H4 gas produced by coal samples treated with different slurry materials at different temperatures;
[0022] Figure 2 To analyze the concentration of CO2 gas produced by coal samples treated with different slurry materials at different temperatures;
[0023] Figure 3 The concentration analysis of carbonyl (C=O) content of coal samples treated with different slurry materials at different temperatures;
[0024] Figure 4 The concentration analysis of hydroxyl (-OH) content of coal samples treated with different slurry materials at different temperatures;
[0025] Figure 5a This is the SEM image of the raw coal sample;
[0026] Figure 5b is the SEM image of the coal sample treated with fly ash slurry material;
[0027] Figure 5c This is the SEM image of the coal sample treated with yellow mud slurry material;
[0028] Figure 5d This is a SEM image of a coal sample treated with the slurry material described in Example 1 of the present application;
[0029] Figure 6 This is the stability analysis result diagram of different slurry materials;
[0030] Figure 7 Figure 2 is a study on the fire extinguishing performance of different slurry materials. DETAILED DESCRIPTION
[0031] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0032] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0033] The embodiment of the present application provides a slurry material for inhibiting spontaneous combustion of coal, comprising the following preparation raw materials, fly ash, carbon dioxide and water; the mass content of calcium oxide in the fly ash is ≥17%.
[0034] The slurry material described in the present application has good wrapping properties for the coal waste, can increase the temperature of characteristic combustion gases such as CO and C2H4, and increase the spontaneous combustion ignition temperature of the coal waste. In addition, the slurry material described in the present application can maintain a high degree of integrity even after losing water, without cracks, and has good sealing properties.
[0035] In addition, the slurry material described in this application uses fly ash, a solid waste discharged by coal-fired power companies, carbon dioxide in waste flue gas, and underground coal mine wastewater as raw materials, which improves the solid waste utilization rate of fly ash, reduces carbon dioxide emissions, and is beneficial to the improvement and maintenance of the ecological environment quality of the mining area.
[0036] In some embodiments of the present application, the weight ratio of the fly ash to the water is: (30-40): (70-80), such as 30:70, 30:75, 30:80, 35:70, 35:75, 35:80, 40:70, 40:80, etc. As the slurry concentration increases, the pH value also increases, and at the same time, OH - When the slurry concentration is greater than 30%, the OH in the slurry - The precipitation rate is almost unaffected by the concentration. In addition, when the fly ash slurry mass concentration is about 30%, the fluidity and the wear on the pipeline are optimal.
[0037] In some embodiments of the present application, the amount of carbon dioxide added is sufficient to make the pH of the slurry material 7-7.5, for example, pH 7, pH 7.2, pH 7.3, pH 7.5, etc. After the pH value of the slurry material drops to 7.5, its alkali return will not exceed 9, which meets the standards for industrial solid waste storage and landfill specified in GB18599-2020.
[0038] In some embodiments of the present application, the mass content of calcium oxide in the fly ash is 17%-20%, the mass content of silicon dioxide is 40%-50%, and the mass content of aluminum oxide is 19%-25%.
[0039] The present application also provides a method for preparing the slurry material for inhibiting spontaneous combustion of coal according to the first aspect of the present application, comprising the following steps:
[0040] (1) mixing fly ash and water to obtain a suspension;
[0041] (2) Under stirring conditions, carbon dioxide is introduced into the suspension to obtain the slurry material.
[0042] The preparation process of the slurry material for inhibiting coal spontaneous combustion described in the present application is simple and suitable for industrial production.
[0043] In some embodiments of the present application, in step (1), the mixing temperature is 20-30°C, for example, 20°C, 25°C, 28°C, 30°C, etc., and the mixing stirring speed is 1400-1500r / min, for example, 1400r / min, 1450r / min, 1480r / min, 1500r / min, etc.
[0044] In some embodiments of the present application, in step (2), the stirring speed is 1400-1500r / min, for example, 1400r / min, 1450r / min, 1480r / min, 1500r / min, etc., and the stirring temperature is 20-30℃, for example, 20℃, 25℃, 28℃, 30℃, etc.
[0045] In some embodiments of the present application, in step (2), the introduction rate of carbon dioxide is 1-2 L / min, for example, 1 L / min, 1.5 L / min, 1.8 L / min, 2 L / min, etc.
[0046] The embodiments of the present application also provide an application of the slurry material for inhibiting coal spontaneous combustion described in the first aspect of the present application or the slurry material for inhibiting coal spontaneous combustion obtained by the preparation method described in the second aspect of the present application in preventing coal spontaneous combustion in mines.
[0047] The slurry material for inhibiting spontaneous combustion of coal described in the present application has a good fire prevention and fire extinguishing effect, can effectively prevent the spontaneous combustion of coal in mines, is easy to use, and has a long-lasting effect.
[0048] In some embodiments of the present application, the application is to spray the slurry material onto the surface of coal to prevent its spontaneous combustion.
[0049] In some embodiments of the present application, the weight ratio of the slurry material to the coal is (2-4):10, for example, 2:10, 3:10, 4:10, etc.
[0050] The technical solution of the present application is described in detail below in conjunction with specific embodiments and drawings.
[0051] Example 1
[0052] A method for preparing a slurry material for inhibiting spontaneous combustion of coal comprises the following steps:
[0053] 30 g of fly ash (the main chemical components of fly ash are: 17.77% by mass of calcium oxide, 46.89% by mass of silicon dioxide, 19.48% by mass of aluminum oxide, 1.64% by mass of potassium oxide, 0.89% by mass of sodium oxide, 1.05% by mass of magnesium oxide, 9.39% by mass of iron oxide, 0.85% by mass of phosphorus pentoxide, and 0.76% by mass of sulfur trioxide) and 80 g of water were mixed at a temperature of 25° C. and a stirring speed of 1400 r / min to obtain a suspension, and carbon dioxide was introduced into the above suspension at a rate of 2 L / min and stirred and mixed at a temperature of 25° C. and a stirring speed of 1400 r / min to obtain a slurry material with a pH of 7.0.
[0054] Example 2
[0055] A method for preparing a slurry material for inhibiting spontaneous combustion of coal comprises the following steps:
[0056] 30 g of fly ash (the main chemical components of fly ash are: 17.77% by mass of calcium oxide, 46.89% by mass of silicon dioxide, 19.48% by mass of aluminum oxide, 1.64% by mass of potassium oxide, 0.89% by mass of sodium oxide, 1.05% by mass of magnesium oxide, 9.39% by mass of iron oxide, 0.85% by mass of phosphorus pentoxide, and 0.76% by mass of sulfur trioxide) and 70 g of water were mixed at a temperature of 25° C. and a stirring speed of 1400 r / min to obtain a suspension, and carbon dioxide was introduced into the above suspension at a rate of 2 L / min and stirred and mixed at a temperature of 25° C. and a stirring speed of 1400 r / min to obtain a slurry material with a pH of 7.2.
[0057] Example 3
[0058] A method for preparing a slurry material for inhibiting spontaneous combustion of coal comprises the following steps:
[0059] 40g of fly ash (the main chemical components of fly ash are: 17.77% by mass of calcium oxide, 46.89% by mass of silicon dioxide, 19.48% by mass of aluminum oxide, 1.64% by mass of potassium oxide, 0.89% by mass of sodium oxide, 1.05% by mass of magnesium oxide, 9.39% by mass of iron oxide, 0.85% by mass of phosphorus pentoxide, and 0.76% by mass of sulfur trioxide) and 70g of water were mixed at a temperature of 25°C and a stirring speed of 1400r / min to obtain a suspension, and carbon dioxide was introduced into the above suspension at a rate of 2L / min and stirred and mixed at a temperature of 25°C and a stirring speed of 1400r / min to obtain a slurry material with a pH of 7.5.
[0060] Comparative Example 1
[0061] A method for preparing a slurry material for inhibiting spontaneous combustion of coal comprises the following steps:
[0062] 30 g of yellow mud and 70 g of water were mixed at a temperature of 25°C and a stirring speed of 1400 r / min to obtain a yellow mud slurry material.
[0063] Comparative Example 2
[0064] A method for preparing a slurry material for inhibiting spontaneous combustion of coal comprises the following steps:
[0065] 30 g of fly ash and 70 g of water were mixed at a temperature of 25° C. and a stirring speed of 1400 r / min to obtain a fly ash slurry material.
[0066] Performance study of slurry materials for preventing and inhibiting spontaneous combustion of coal as described in Examples 1-3 of the present application.
[0067] The slurry materials for inhibiting spontaneous combustion of coal prepared in Example 1 and Comparative Examples 1-2 of the present application were uniformly sprayed on three coal samples, and the mass ratio of the slurry material to the coal sample was 3: 10. The three coal samples sprayed with the slurry material were placed in a muffle furnace, and the temperature, gas composition and other data at each stage of the muffle furnace heating process were detected and recorded using an electron spin resonance spectrometer.
[0068] The coal samples used in the test of this application are a mixture of coal samples with particle sizes of 0.9mm, 3mm, 5mm, 7mm and 9mm in equal parts by mass.
[0069] 1. Analysis of the concentration of C2H4 gas produced by coal samples during the test
[0070] The concentration of C2H4 gas produced by coal samples treated with different slurry materials at different temperatures is as follows: Figure 1 shown.
[0071] from Figure 1 It can be seen that: the raw coal sample without slurry material treatment produces C2H4 gas when the temperature rises to 120°C; the coal sample treated with yellow mud slurry material produces C2H4 gas when the temperature rises to 130°C; the coal sample treated with fly ash slurry material and mineralized fly ash slurry material (the slurry material described in Example 1 of the present application) produces C2H4 gas when the temperature rises to 140°C. Figure 1 It can be seen that the process of producing C2H4 in the coal samples treated with the yellow mud slurry material, fly ash slurry material and the slurry material described in Example 1 of the present application has an obvious lag effect compared with the original coal samples. The delayed effect of the appearance of C2H4 in the oxidation and heating process of the coal samples treated with the slurry material described in Example 1 of the present application is the most obvious, and the flame retardant effect on the coal samples is better than that of yellow mud slurry and fly ash slurry.
[0072] 2. Analysis of CO2 gas concentration generated by coal samples during the test
[0073] The concentration of CO2 gas produced by coal samples treated with different slurry materials at different temperatures is as follows: Figure 2 shown.
[0074] from Figure 2 It can be seen that before the heating temperature reaches 80°C, the amount of CO2 produced by the four groups of different coal samples is small and the growth rate is slow. When the temperature of the coal sample exceeds 80°C, the rate of CO2 production by the original coal sample, the coal sample treated with the yellow mud slurry material, and the coal sample treated with the fly ash slurry material begins to accelerate, and when the temperature of the coal sample reaches 130°C, the rate of CO2 production begins to increase sharply, while the coal sample treated with the mineralized fly ash slurry material (the slurry material described in Example 1 of the present application) begins to slowly produce CO2 when the coal sample temperature reaches 130°C. Compared with the coal sample treated with the yellow mud slurry material and the coal sample treated with the fly ash slurry material, the coal sample treated with the slurry material described in Example 1 of the present application has the lowest CO2 production rate, that is, the slurry material described in Example 1 of the present application can more effectively inhibit the full combustion of the coal body.
[0075] 3. Quantitative analysis of carbonyl (C=O) contained in coal samples during the test
[0076] The changes in the carbonyl (C=O) content of coal samples treated with different slurry materials at different temperatures are shown in Figure 2. Figure 3 shown.
[0077] The carbonyl (C=O) functional group content indicates the generation of organic matter after coal spontaneous combustion. An increase in the carbonyl (C=O) content indicates that the coal spontaneously combusts more fully.
[0078] from Figure 3It can be seen that when the temperature of the coal sample rises from 30°C to 80°C, the content of C=O (carbonyl) in the original coal sample increases significantly, the content of C=O (carbonyl) in the coal samples treated with yellow mud slurry material, the coal samples treated with fly ash slurry material and the coal samples treated with mineralized fly ash slurry material (the slurry material described in Example 1 of the present application) increases slowly, and the increase in C=O (carbonyl) in the coal sample treated with the slurry material described in Example 1 of the present application is the smallest, that is, the slurry material described in Example 1 of the present application has the strongest inhibitory effect on the spontaneous combustion process of coal oxidation.
[0079] 4. Quantitative analysis of hydroxyl groups (-OH, an important participating group in the low-temperature oxidation reaction of coal) contained in coal samples during the test
[0080] The changes in the content of hydroxyl (-OH) in coal samples treated with different slurry materials at different temperatures are shown in Figure 2. Figure 4 shown.
[0081] from Figure 4 It can be seen that: with the increase of temperature, the -OH content in the coal samples shows an overall downward trend, and there are certain differences in the degree of decline of different coal samples. When the coal sample temperature is 80-130℃, the -OH content in the coal samples treated with yellow mud slurry material decreases slowly, and after the coal sample temperature reaches 130℃, the -OH content in the coal samples treated with yellow mud slurry material decreases more rapidly. It may be due to the fact that the water in the yellow mud slurry material evaporates and absorbs the heat of the coal sample during the early heating process, slowing down the oxidation process of the coal sample; and as the temperature continues to rise, the water in the yellow mud slurry material is exhausted, which greatly weakens its inhibitory effect on coal oxidation, and the coal samples treated with fly ash slurry material have a similar situation. The coal samples treated with mineralized fly ash slurry material (the slurry material described in Example 1 of the present application) have similar initial inhibition effects to those of the fly ash slurry material. However, as the temperature of the coal samples increases (temperature is higher than 130°C), the decreasing trend of the -OH content in the coal samples treated with the mineralized fly ash slurry material (the slurry material described in Example 1 of the present application) is much slower than that of the other three coal samples. In addition, the -OH content in the coal samples treated with the mineralized fly ash slurry material is consumed the least, which is much less than that of the coal samples treated with the raw coal and other slurry materials. That is, the slurry material described in the present application has a good effect in inhibiting coal oxidation.
[0082] 5. SEM analysis of different coal samples
[0083] The SEM image of the raw coal sample is as follows Figure 5a As shown in the SEM image of the coal sample treated with fly ash slurry material Figure 5b As shown in the SEM image of the coal sample treated with yellow mud slurry material Figure 5c As shown, the SEM image of the coal sample treated with the mineralized fly ash slurry material (the slurry material described in Example 1 of the present application) is as follows Figure 5d shown.
[0084] from Figure 5a-5d It can be seen that the raw coal particles are small and dispersed, with irregular surfaces and large specific surface areas, and the specific surface area exposed to oxygen is large. The surface of the coal samples treated with yellow mud slurry materials, the coal samples treated with fly ash slurry materials, and the coal samples treated with mineralized fly ash slurry materials (the slurry materials described in Example 1 of the present application) all have an adhesion layer, which adsorbs on the surface of the coal samples to block direct contact between oxygen and the surface of the coal samples, thus achieving the macroscopic characteristic of covering the surface of the coal samples to inhibit coal spontaneous combustion.
[0085] However, the yellow mud slurry material and the fly ash slurry material will lose water due to the increase in temperature, causing cracks in the adhesion layer, resulting in a reduction in the effect of inhibiting coal spontaneous combustion. However, the adhesion layer produced by the coal sample treated with the mineralized fly ash slurry material (the slurry material described in Example 1 of the present application) will not have this phenomenon. After being subjected to high temperature (the temperature at which the coal is completely burned), the adhesion layer still has a high degree of density and relatively few surface cracks. That is, the coal sample treated with the slurry material described in Example 1 of the present application has a better anti-spontaneous combustion effect.
[0086] 6. Stability study of different slurry materials
[0087] The same amount of yellow mud slurry material, fly ash slurry material and mineralized fly ash slurry material (the slurry material described in Example 1 of the present application) were placed in the same environment, and the changes in the macroscopic cracks of the different slurry materials were observed after 15 days. The results are as follows: Figure 6 shown.
[0088] from Figure 6 It can be seen that ( Figure 6 From left to right in the figure are yellow mud slurry material, fly ash slurry material and mineralized fly ash slurry material): Under the same incubation conditions, after each sample was placed for 15 days, cracks appeared in the yellow mud slurry material, fly ash slurry material and mineralized fly ash slurry material (the slurry materials described in Example 1 of the present application), among which the degree of crack development in the yellow mud slurry material was the largest, followed by the fly ash slurry material. That is, the slurry materials described in the present application have a stronger density, and the crack development characteristics are also slower with the increase of time.
[0089] 7. Study on fire extinguishing performance of different slurry materials
[0090] Research method: Three portions of coal with the same properties and the same amount are placed in a heating box, and oxygen is introduced into the box to simulate the spontaneous combustion of the coal. When the coal temperature in the box reaches 800°C, the same amount of yellow mud slurry, fly ash slurry, and the slurry described in Example 1 are introduced into the box respectively, so that the slurry completely covers the coal (the mass ratio of slurry to coal at this time is 3.5:10). The time it takes for different slurries to reduce the temperature of the coal to normal and stable is observed and recorded.
[0091] The results are as follows Figure 7 shown.
[0092] from Figure 7 It can be seen that under the same circumstances, when yellow mud slurry material is used for fire extinguishing, it takes 340 seconds until the coal temperature reaches a normal and stable state, when fly ash slurry material is used for fire extinguishing, it takes 330 seconds until the coal temperature reaches a normal and stable state, and when mineralized fly ash slurry material (the slurry material described in Example 1 of the present application) is used for fire extinguishing, it takes 310 seconds until the coal temperature reaches a normal and stable state, that is, the slurry material described in Example 1 of the present application has a better coal fire extinguishing effect.
[0093] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A slurry material for inhibiting spontaneous combustion of coal, characterized in that: The method comprises the following preparation raw materials, fly ash, carbon dioxide and water; The mass content of calcium oxide in the fly ash is ≥17%.
2. The slurry material for inhibiting spontaneous combustion of coal according to claim 1, characterized in that: The weight ratio of the fly ash to the water is: (30-40): (70-80); And / or, the amount of carbon dioxide added is sufficient to make the pH of the slurry material be 7-7.
5.
3. The slurry material for inhibiting spontaneous combustion of coal according to claim 1, characterized in that: The mass content of calcium oxide in the fly ash is 17%-20%, the mass content of silicon dioxide is 40%-50%, and the mass content of aluminum oxide is 19%-25%.
4. The method for preparing the slurry material for inhibiting spontaneous combustion of coal according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) mixing fly ash and water to obtain a suspension; (2) Under stirring conditions, carbon dioxide is introduced into the suspension to obtain the slurry material.
5. The method for preparing the slurry material for inhibiting spontaneous combustion of coal according to claim 4, characterized in that: In step (1), the mixing temperature is 20-30° C., and the mixing stirring speed is 1400-1500 r / min.
6. The method for preparing the slurry material for inhibiting spontaneous combustion of coal according to claim 4, characterized in that: In step (2), the stirring speed is 1400-1500 r / min, and the stirring temperature is 20-30°C.
7. The method for preparing the slurry material for inhibiting spontaneous combustion of coal according to claim 4, characterized in that: In step (2), the carbon dioxide is introduced at a rate of 1-2 L / min.
8. Use of the slurry material for inhibiting coal spontaneous combustion according to any one of claims 1 to 3 or the slurry material for inhibiting coal spontaneous combustion obtained by the preparation method according to any one of claims 4 to 7 in preventing coal spontaneous combustion in mines.
9. The use according to claim 8, characterized in that: The application is to spray the slurry material onto the surface of coal to prevent it from spontaneous combustion.
10. The use according to claim 9, characterized in that: The weight ratio of the slurry material to the coal is (2-4):10.